Competitiveness and knowledge : an international comparison of traditional firms /: an international comparison of traditional firms. (2017) - Cader, Hanas; Sales, Maria de Fátima; Similä, Jan Ole; Staduto, Jefferson Andronio Ramundo; Westeren, Knut Ingar
No abstract available